2014
DOI: 10.7575/aiac.ijalel.v.4n.2p.39
|View full text |Cite
|
Sign up to set email alerts
|

On the Practicality of Group Dynamic Assessment: A Seminal Enterprise Deserving Closer Scrutiny

Abstract: This paper is a preliminary study designed to scrutinize the way Group Dynamic Assessment (G-DA), suggested by Poehner (2009), has been implemented in L2 classrooms regarding its basic premise: moving the group forward in its ZPD while benefiting individuals as well. Since the one-to-one interaction that characterizes DA framework represents an unrealistic model for classroom teachers who must manage classes of 15 to 30 learners, Poehner (2009) suggests the use of DA with groups of L2 learners rather than indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Their findings showed that G-DA enhanced the development of listening comprehension ability especially the pragmatic understanding of conversational implicates among intermediate EFL learners. Saneiei, Birjandi, and Abdollahzadeh (2015) believed that dynamic assessment offers a conceptual framework which integrates assessment into instruction and posits that learners' responsiveness to instruction can be seen as a measure of learners' potential.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings showed that G-DA enhanced the development of listening comprehension ability especially the pragmatic understanding of conversational implicates among intermediate EFL learners. Saneiei, Birjandi, and Abdollahzadeh (2015) believed that dynamic assessment offers a conceptual framework which integrates assessment into instruction and posits that learners' responsiveness to instruction can be seen as a measure of learners' potential.…”
Section: Literature Reviewmentioning
confidence: 99%